Highly Proficiency Learners on Noticing Strategy towards Corrective Feedback: Pembelajar Sangat Mahir dalam Memperhatikan Strategi menuju Umpan Balik Korektif - Mufanti, Restu (JEES (Journal of English Educators Society), 2016)
This study primarily aims at capturing the nature of how highly proficiency learners (HPLs) employ noticing strategies in processing the indirect corrective feedback. The results of this study can be adapted by others learners to apply the strategy used by HPLs in noticing corrective feedback so that they can improve their writing ability. To meet the goal, a study on the way highly proficiency learners notice indirect corrective feedback that focused on three language aspects, i.e., lexis, grammar, and content was conducted. Observation and in depth- interview were used as the instruments to collect the data. The subjects chosen were six students who have a good performance on their writing. This study revealed that the HPLs are able to employ various noticing strategies when they are processing the indirect corrective feedback. They seem more cognizant of the problems they encounter and more capable of taking an action to respond the feedback given. Some noticing strategies are identified to apply in processing the feedback that are suited on the nature of the problems, such as by making any comparison, connection, correlation, identification of error, recalling the past experience/ knowledge and self-inquiry. However, three aspects that often applied by HPLs are identification of error well, recalling the past knowledge and self-inquiry.